STUDIES ON FECUNDITY, SEX RATIO AND CROSSBREEDING IN DIFFERENT STRAINS OF GUPPY - PALAV, A. D.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
Studies on the fecundity, sex ratio and crossbreeding in differentstrains of the guppy Poecilia reticulata such as Butterfly I, Butterfly IIand Cobra strains was carried out. The highest fecundity among ButterflyI strain was at the 5th breed while it was highest at the 6th and 8th breedamong Butterfly II and Cobra strain respectively. The average malepercentage was 39.88%, 43.39% and 45.02% among Butterfly I, Butterfly IIand Cobra strains respectively. The crossbreeding of strains showed goodresults among crossbreeds of ButterflyQII ( ~) X Cobra ( (1) and ButterflyI(~) X Cobra ( (1 ). The crossbreed among the Butterfly I(~) X Cobra ( 8)proved to be excellent from the point of view of more percentage, rapidgrowth, and brilliant body and finnage colouration.